Cell Isolation Induces Fate Changes of Bone Marrow Mesenchymal Cells Leading to Loss or Alternatively to Acquisition of New Differentiation Potentials. (15th July 2014) - Shoshani, Ofer; Ravid, Orly; Massalha, Hassan; Aharonov, Alla; Ovadya, Yossi; Pevsner‐Fischer, Meirav; Leshkowitz, Dena; Zipori, Dov
Abstract Mesenchymal stromal cell populations include a fraction, termed mesenchymal stem cells, exhibiting multipotency. Other cells within this population possess a lesser differentiation range. This was assumed to be due to a mesenchymal cellular cascade topped by a multipotent cell, which gives rise to progeny with diminishing differentiation potentials. Here, we show that mesenchymal cells, a priori exhibiting a limited differentiation potential, may gain new capacities and become multipotent following single‐cell isolation. These fate changes were accompanied by upregulation of differentiation promoting genes, many of which also became H4K20me1 methylated. Early events in the process included TGFβ and Wnt modulation, and downregulation of hypoxia signaling. Indeed, hypoxic conditions inhibited the observed cell changes. Overall, cell isolation from neighboring partners caused major molecular changes and particularly, a newly established epigenetic state, ultimately leading to the acquisition of new differentiation potentials and an altered cell fate. Stem Cells2014;32:2008–2020